Brönsted Acid of Keggin Type Polyoxometalate Catalyzed Pinacol Rearrangement - Risfidian Mohadi; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
Keggin type polyoxometalates K4[a-SiW12O40] was synthesized and transformed to H4[a-SiW12O40]. Both catalysts have been used for pinacol rearrangement in toluene at 373 oK. The results showed that reaction of pinacol rearrangement did not proceed using K4[a-SiW12O40] as catalyst. The extent reac-tion time until 20 h also did not produce pinacolone as main product. By using H4[a-SiW12O40] as cata-lyst at 1 h reaction time gave conversion 100% with formation of pinacolone 72%. The reaction produce 27% of 2,3-dimethyl-1,3-butadiene as byproduct and 99% carbon balance for the reaction. This phe-nomenon indicated the Brönsted acid is a key role for catalytic reaction of pinacol rearrangement to pinacolone. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)